2022
DOI: 10.3126/ajn.v6i1.47957
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Weed Management in Summer Maize in Mid-Hills of Nepal

Abstract: Weed is one of the major problems in maize production. To develop an appropriate weed management practice, a field experiment was carried out during 2017 and 2018 at Khumaltar. Twelve different treatments, Pendimethalin as pre @ 1.0 kg a.i ha-1, Atrazine as pre @ 1 kg a.i ha-1, Metribuzine as pre @ 0.5 kg a.i ha-1, Tembotrione as post @ 0.2 kg a.i ha-1,  Pendimethalin followed by (fb) 1 HW, Atrazine fb 1 HW, Metribuzine fb 1 HW, Tembotrione fb 1 HW,  Atrazine + Metribuzine (early post ) as tank mixed, Straw mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Several authors have experimented varying Napplication time on maize crop. Bhattarai et al (2014) reported maximized yield of corn grain from 3 split equal doses up to 60 kg/ha nitrogen applied at sowing, earthling up and silking stages respectively. Peak grain yield and increased yield of plant biomass has been reported on application of 80 kg N/ha in two split doses (first as basal application at planting, second as side-dress during knee-high stage respectively), which result to a higher cost-benefit ratio of 1:5 (Nurudeen et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Several authors have experimented varying Napplication time on maize crop. Bhattarai et al (2014) reported maximized yield of corn grain from 3 split equal doses up to 60 kg/ha nitrogen applied at sowing, earthling up and silking stages respectively. Peak grain yield and increased yield of plant biomass has been reported on application of 80 kg N/ha in two split doses (first as basal application at planting, second as side-dress during knee-high stage respectively), which result to a higher cost-benefit ratio of 1:5 (Nurudeen et al, 2015).…”
Section: Introductionmentioning
confidence: 97%